2018
DOI: 10.1155/2018/8214379
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Deficiencies in the Mechanisms of Its Repair: Implications in the Pathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a perplexing and potentially severe disease, the pathogenesis of which is yet to be understood. SLE is considered to be a multifactorial disease, in which genetic factors, immune dysregulation, and environmental factors, such as ultraviolet radiation, are involved. Recently, the description of novel genes conferring susceptibility to develop SLE even in their own (monogenic lupus) has raised the interest in DNA dynamics since many of these genes are linked to DNA repair. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 127 publications
1
16
0
Order By: Relevance
“…Recent evidence indicates that patients with SLE have higher levels of DNA damage than normal subjects, and that polymorphisms in genes involved in the preservation of the genomic stability increase the risk for SLE (32)(33)(34). Furthermore, experience from animal models reinforces the importance of defective repair in the development of SLElike disease (35), suggesting that therapeutic potential of targeting DNA damage and DNA repair responses in SLE pathogenesis (36,37). Indeed, oxidized DNA has a greater immunostimulatory capacity to stimulate type I IFN than does normal DNA, possibly due to increased resistance to degradation by the 3 ′ repair exonuclease 1 TREX 1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that patients with SLE have higher levels of DNA damage than normal subjects, and that polymorphisms in genes involved in the preservation of the genomic stability increase the risk for SLE (32)(33)(34). Furthermore, experience from animal models reinforces the importance of defective repair in the development of SLElike disease (35), suggesting that therapeutic potential of targeting DNA damage and DNA repair responses in SLE pathogenesis (36,37). Indeed, oxidized DNA has a greater immunostimulatory capacity to stimulate type I IFN than does normal DNA, possibly due to increased resistance to degradation by the 3 ′ repair exonuclease 1 TREX 1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a genetic analysis of chromosome 1q41-q42 revealed that a specific allele of PARP1, with a length of approximately 85bp, confers defective DNA repair and abnormal apoptosis, thus predisposing to SLE [114]. The contribution of polymorphisms in DDR/R components to the development and progression of SLE has been recently reviewed here [115].…”
Section: Gene Polymorphisms Associated With Impaired Dna Repair Machimentioning
confidence: 99%
“…The present study's distinguished findings were that the male gender and G/G genotype have 4.6-and 3.5-times higher odds with exhibit anemia, respectively. This may be a manifestation of the enhanced effect of some environmental factors such as exposure to UV as a cofactor for DNA damage repair defects associated with G allele genotype in the Caucasian population, associated with the severity of some autoimmune manifestations [40]. The statistical analysis performing SNP exact test for Hardy-Weinberg equilibrium revealed that the p-value for the control group was 0.49 (Insignificant), which means that the requirement of Hardy-Weinberg equilibrium exists.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, negative regulation of the genes encoding the proteins involved in the NER pathway in SLE patients, specifically DDB1, ERCC2, XPA, and XPC, has been found [40].…”
Section: Discussionmentioning
confidence: 99%